Patient Safety Over Power Hierarchy: A Scoping Review of Healthcare Professionals' Speaking-up Skills Training. Issue 5 (September 2020) - Kim, Sara; Appelbaum, Nital P.; Baker, Neil; Bajwa, Nadia M.; Chu, Frances; Pal, Jay D.; Cochran, Nancy E.; Bochatay, Naike
Abstract : ABSTRACT: Communication failures in healthcare constitute a major root cause of adverse events and medical errors. Considerable evidence links failures to raise concerns about patient harm in a timely manner with errors in medication administration, hygiene and isolation, treatment decisions, or invasive procedures. Expressing one's concern while navigating the power hierarchy requires formal training that targets both the speaker's emotional and verbal skills and the receiver's listening skills. We conducted a scoping review to examine the scope and components of training programs that targeted healthcare professionals' speaking-up skills. Out of 9, 627 screened studies, 14 studies published between 2005 and 2018 met the inclusion criteria. The majority of the existing training exclusively relied on one-time training, mostly in simulation settings, involving subjects from the same profession. In addition, most studies implicitly referred to positional power as defined by titles; few addressed other forms of power such as personal resources (e.g., expertise, information). Almost none addressed the emotional and psychological dimensions of speaking up. The existing literature provides limited evidence identifying effective training components that positively affect speaking-up behaviors and attitudes. Future opportunities include examining the role of healthcare professionals' conflict engagement style or leaders' behaviors as factors that promote speaking-up behaviors. Abstract : Supplemental Digital Content is Available in the Text.